2009
DOI: 10.1038/nature08517
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of asthenospheric mantle and melt extraction rates at mid-ocean ridges

Abstract: Magmatic production on Earth is dominated by asthenospheric melts of basaltic composition that have mostly erupted at mid-ocean ridges. The timescale for segregation and transport of these melts, which are ultimately responsible for formation of the Earth's crust, is critically dependent on the permeability of the partly molten asthenospheric mantle, yet this permeability is known mainly from semi-empirical and analogue models. Here we use a high-pressure, high-temperature centrifuge, at accelerations of 400g-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 34 publications
8
64
0
Order By: Relevance
“…Although the exact timing of melt segregation might slightly differ with known variations of n and τ from the literature (e.g. von Bargen & Waff 1986;Wark & Watson 1998;Cheadle et al 2004;Connolly et al 2009), the general findings of our model are robust. In our model the viscosity of both the silicate and the iron melt is chosen to be 1 Pa s, similar to e.g.…”
Section: Summary and Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Although the exact timing of melt segregation might slightly differ with known variations of n and τ from the literature (e.g. von Bargen & Waff 1986;Wark & Watson 1998;Cheadle et al 2004;Connolly et al 2009), the general findings of our model are robust. In our model the viscosity of both the silicate and the iron melt is chosen to be 1 Pa s, similar to e.g.…”
Section: Summary and Discussionsupporting
confidence: 55%
“…For isotropic systems the values n = 2 and τ ≈ 1600 to 3000 have been derived numerically (von Bargen & Waff 1986;Cheadle et al 2004), whereas experimental data yield n ≈ 3 and τ ≈ 10 to 270 (Wark & Watson 1998;Connolly et al 2009). …”
Section: Melt Generation Melt Heat Transport and Differentiationmentioning
confidence: 99%
“…Values for κ are less well constrained, but estimates range from 10 −15 το 10 −10 m 2 for partially molten mantle peridotite, depending upon the local melt fraction (Connolly et al, 2009;Sundberg et al, 2010). The largest volume of the plume head is likely characterized by melt fractions less than 3%, which would imply permeability values of order 10 −11 -10 −14 m 2 .…”
Section: Physical Mechanisms Of Triggering and Magmatic Response Timementioning
confidence: 99%
“…Gravity-driven melt transportation is proportional to hydrostatic melt mobility, Dr/Z, where Z is the viscosity of the melt and Dr is density contrast between the melt and the surrounding solid rock, in addition to the permeability of the rock 20,31,32 . The study by Sakamaki et al 20 discussed the mobility of the basalt melt in the upper mantle and showed that Dr/Z changes from 0.03 to 0.58 g cm À 3 Pa À 1 s À 1 at 0-210 km depth.…”
Section: Article Nature Communications | Doi: 101038/ncomms6091mentioning
confidence: 99%
“…These viscosities are so low that they are more similar to water 30 than to silicate melts 20 . Gravity-driven melt transportation (that is, without considering effects of shear deformation) is proportional to 'hydrostatic melt mobility', Dr/Z, where Z is the viscosity of the melt and Dr is density contrast between the melt and the surrounding solid rock, in addition to the permeability of the rock 20,31,32 . We find that the mobility of carbonate melts is B2-3 orders of magnitude higher than that of basalt melts 20 .…”
mentioning
confidence: 99%